Emerging Roles of Green-Synthesized Chalcogen and Chalcogenide Nanoparticles in Cancer Theranostics - Femi Olawale; Olakunle Oladimeji; Mario Ariatti; Moganavelli Singh (Journal of Nanotechnology)
The last few decades have seen an overwhelming increase in the amount of research carried out on the use of inorganic nanoparticles. More fascinating is the tremendous progress made in the use of chalcogen and chalcogenide nanoparticles in cancer theranostics. These nanomaterials, which were initially synthesized through chemical methods, have now been efficiently produced using different plant materials. The paradigm shift towards the biogenic route of nanoparticle synthesis stems from its superior advantages of biosafety, eco-friendliness, and simplicity, among others. Despite a large number of reviews available on inorganic nanoparticle synthesis through green chemistry, there is currently a dearth of information on the green synthesis of chalcogens and chalcogenides for cancer research. Nanoformulations involving chalcogens such as sulfur, selenium, and tellurium and their respective chalcogenides have recently emerged as promising tools in cancer therapeutics and diagnosis. Similar to other inorganic nanoparticles, chalcogens and chalcogenides have been synthesized using plant extracts and their purified biomolecules. In this review, we provide an up-to-date discussion of the recent progress that has been made in the plant-mediated synthesis of chalcogens and chalcogenides with a special focus on their application in cancer theranostics.